Environmental aesthetics in China: East West dialogue - Rolston, Holmes, 1932-2025, speaker; Unidentified speaker (Colorado State University. Libraries, 2015)
Lecture by Holmes Rolston III presented in Wuhan, China, at the Environmental Aesthetics and Beautiful China International Conference, May 20-23, 2015. 1. Art and Nature: Chinese Landscape as a Work of Art? 2. Urban, Rural, Wild: Are the Chinese Three Dimensional Persons? 3. Residence in Place: Is China Like No Place Else on Earth? 4. Ugly? What on Chinese Landscapes Is Ugly? 5. Environmental Aesthetics and Ecological Aesthetics: Beautiful China, Ecosystemic China? 6. Environmental Aesthetics and Environmental Policy: Beautiful China, Saving China?
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental aesthetics; China; art and nature; agricultural landscapes; humanized nature; wilderness in China; ecosystems and aesthetics; environmental policy; aesthetics and conservation; aesthetics East and West